Characteristics and challenges of the nopal vegetable cultivation system in Cuautlacingo, Otumba - Flores-Sánchez, Diego; Reyes-Terrazas, Ana Surazi; Navarro-Garza, Hermilio; Pérez-Olvera, Ma. Antonia; Almaguer-Vargas, Gustavo (Revista Mexicana de Ciencias Agrícolas, 2023)
The State of Mexico is the third producer of nopal vegetable nationwide, Otumba concentrates 57% of state production. In the decade 2010-2020 the area increased by 27%, with a 44% increase in production. However, it faces a number of socioeconomic and technical constraints. The objective of the research was to diagnose the nopal vegetable cultivation systems in Cuautlacingo, Otumba and propose strategies to improve their functioning. Work was carried out with 47 cooperating producers to whom a questionnaire structured in the following three axes was applied: 1) socioeconomic characteristics of the production units; 2) characteristics of the nopal vegetable cultivation system; and 3) technical schedule of the nopal vegetable cultivation system. Through a cluster analysis, two groups of producers were identified, the problems they face are incidence of pests and diseases, low technification, poor organization and marketing channels, need for training and technical accompaniment and lack of government impulse. It is recommended to join efforts to plan actions, attend and develop the production niches of the region and seek alternatives to increase the competitiveness of nopal vegetable.
Keywords: charaterization; farmers' s group; technical itinerary; family production units